Effects of Intraperitoneal and Intrathecal Morphine Analgesia on the Expression of μ-Opioid Receptors in Bone Cancer Pain Rats. Issue 4 (14th October 2019) - Liu, Wei; Liu, Heqi; Zhang, Zongde; Huang, Jiapeng
Backgrounds: This study compared analgesic effects and μ-opioid receptor expression levels during long-term intraperitoneal and intrathecal treatment in a bone cancer pain rat. Methods: Twenty-four female Sprague-Dawley rats were injected Walker 256 tumor cells into the femur to create a bone cancer pain model. The control group was injected with saline intraperitoneally and intrathecally. The intraperitoneal group was injected with morphine intraperitoneally and saline intrathecally. The intrathecal group was injected saline intraperitoneally and morphine intrathecally. Changes in pain threshold, μ-opioid receptor expression levels in spinal cord, and tumor tissue were compared between 3 groups. Results: The intrathecal morphine group and the intraperitoneal group showed no difference in analgesia effects ( P > .05). Western blot and immunohistochemical staining of μ-opioid receptors demonstrated that its level in the intrathecal group was significantly lower than the intraperitoneal group ( P < .05) and without significant difference with the control group ( P > .05). The expression levels of μ-opioid receptor in the spinal cord tissue did not reveal a difference among these 3 groups ( P > .05). Conclusion: Intrathecal group and intraperitoneal group showed significant difference in μ-opioid receptor expressions although with no difference in analgesia effects. Long-term intrathecal morphine administration provided similar analgesia compared to systemic morphine.